Fiscal Policy Decentralization Innovation in Groundwater Tax Collection: A Study of Policy Implementation in Tebing Tinggi City - Angelia, Nina; Adianto, Adianto; Batubara, Beby Masitho; Nasution, Chairika (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to evaluate the implementation of the groundwater tax collection policy in Tebing Tinggi City within the context of fiscal decentralization and to identify innovations needed to improve its effectiveness. Despite having a legal basis through Regional Regulation No. 1 of 2024, field practice shows that groundwater tax collection still faces various technical and institutional obstacles. The research method used is descriptive qualitative, with data collected through in-depth interviews, direct observation, and review of official documents. The analytical framework refers to George C. Edward III's policy implementation model, which includes four main components: information delivery, resource availability, implementer attitudes, and organizational structure. The research findings indicate that these four elements have not been implemented effectively. Policy information has not been conveyed comprehensively and tends to be one-way; policy implementers work with limited capacity and multiple role burdens; supporting training is not yet available to strengthen implementer commitment; and the existing organizational structure does not adequately support technology-based service innovation. Based on these conditions, a policy reform strategy is needed that includes strengthening public communication, a more structured division of implementing functions, the establishment of a fiscal education unit, and the development of a spatial information system (GIS). This initiative is expected to encourage increased taxpayer compliance and strengthen regional fiscal governance in a sustainable manner.